Bulgarians in the Zaporizhzhia Oblast in Ukraine: the cultural-national identity - Krasowska, Helena (Balcanica Posnaniensia. Acta et studia, 2017)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The Zaporizhzhia oblast was created on 10 January 1939 as part of the Ukrainian Soviet Socialist Republic. As is generally known territories of this province were previously belonged to the Golden Horde and from 1554 year to the Crimean Khanate. From the XV to the XVII century northern part of Zaporozhzhia was the Zaporozhian Sich. The presence of the Bulgarian minority living today on the territory of the Zaporizhzhia oblast dates back to the second half of the XIX century. In the years 1861–1862 the Bessarabian Bulgarians established in these areas 34 villages and the Bulgarians from Vidin established 2. There were established 36 Bulgarian villages, now remained 30. After 1990 the Bulgarian cultural societies were created, there are Bulgarian language courses on various levels, the Bulgarian-language press, the folk groups. Bulgaria educates in its universities Ukrainian students of Bulgarian origin, as well as delegates teachers of Bulgarian language to work here. Leaders of the Bulgarian associations are visible in the region and actively participate in the promotion of their own culture.